Comparison of gut microbiota in adult patients with type 2 diabetes and healthy individuals. (October 2017) - Sedighi, Mansour; Razavi, Shabnam; Navab-Moghadam, Fatemeh; Khamseh, Mohammad E.; Alaei-Shahmiri, Fariba; Mehrtash, Amirhosein; Amirmozafari, Nour
Abstract: Recent studies indicate that inflammatory reactions leading to the development of type 2 diabetes mellitus (T2DM) may also contribute to variations in the composition of the intestinal microbiota, suggesting a relation between T2DM and bacterial residents in the intestinal tract. This case-control study was designed to evaluate the composition of the gut microbiota dominant bacterial groups in patients with T2DM compared to the healthy people. A total of 36 adult subjects (18 patients diagnosed with T2DM and 18 healthy persons) were included in the study. The intestinal microbiota composition was investigated by quantitative real-time polymerase chain reaction (qPCR) method using bacterial 16S rRNA gene. The quantities of two groups of bacteria were meaningfully different among T2DM patients and healthy individuals. While, the level of Lactobacillus was significantly higher in the patients with T2DM ( P value < 0.001), Bifidobacterium was significantly more frequent in the healthy people ( P value < 0.001). The quantities of Prevotella ( P value = 0.0.08) and Fusobacterium ( P value = 0.99) genera in faecal samples were not significantly different between the two groups. The significant alterations in dominant faecal bacterial genera found in T2DM patients participating in the current study highlight the link between T2DM disease and compositional variation in intestinal flora. These findings may be valuable for developing approaches to control T2DM by modifying the gut microbiota. More investigations with focus on various taxonomic levels (family, genus and species) of bacteria are necessary to clarify the exact relevance of changes in the gut microbial communities with the progression of T2DM disorder. Highlights: Our results showed that some of gut microbiota composition was different between the T2DM patients and healthy individuals. There is no significant differences in quantity of Prevotella and Fusobacterium genera between T2DM patients and controls. The level of Lactobacillus group was significantly higher in the diabetics compared to the healthy individuals ( P <0.001). Bifidobacterium group was significantly more frequent in the healthy subjects compared with the T2DM patients ( P <0.001). It can be concluded that T2DM disorder is associated with the shifts and fluctuations in the composition of gut microbiota.